Paste resin composition, high thermal conductivity material and semiconductor device
By using a paste resin composition containing specific (meth)acryloyl compounds and metal particles, a high thermal conductivity material is sintered to form a high thermal conductivity material for bonding of semiconductor devices, the problems of unstable conductivity and insufficient long-term reliability of semiconductor devices in the prior art are solved, and good conductivity and long-term reliability are achieved.
Patent Information
- Application Number
- CN202180011544.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-29
- Filing Date
- 2021-01-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-01-21
AI Technical Summary
In the prior art, semiconductor devices have unstable conductivity during long-term use, resulting in insufficient long-term reliability.
A paste-like resin composition containing a (meth)acryloyl compound having a predetermined structure and silver or copper particles is used to form a highly thermally conductive material by sintering, and is used for bonding of a semiconductor element and a substrate.
The semiconductor device maintains good conductivity and excellent long-term reliability in long-term use, and problems such as peeling of the joint portion are suppressed.
Smart Images

Figure BDA0003769535590000031 
Figure BDA0003769535590000191 
Figure FDA0005150063830000011
Abstract
Description
Technical Field
[0001] The present invention relates to a paste-like resin composition, a high thermal conductivity material and a semiconductor device. Background Art
[0002] A technique for producing semiconductor devices using a thermosetting resin composition containing metal particles is known in order to improve the heat dissipation of semiconductor devices. The thermal conductivity of the cured product can be improved by making the thermosetting resin composition contain metal particles having a higher thermal conductivity than the resin.
[0003] As a specific example of application to a semiconductor device, as in the following Patent Documents 1 and 2, there is known a technique for bonding / joining a semiconductor element and a substrate (support member) using a thermosetting resin composition containing metal particles.
[0004] Patent Document 1 discloses a semiconductor bonding thermosetting resin composition containing a (meth)acrylate compound of a predetermined structure, a radical initiator, silver particles, silver powder, and a solvent, and a semiconductor device formed by bonding a semiconductor element and a substrate using the composition. The document states that the connection reliability can be improved with respect to a temperature cycle after mounting (Paragraph 0011).
[0005] Patent Document 2 discloses a paste resin composition containing an imide acrylate compound, a radical initiator, a filler, and a liquid rubber component, and a semiconductor device formed by bonding a semiconductor element and a substrate using the composition. The document states that by reducing the stress of the paste resin composition, the occurrence of chip cracks or chip warpage can be suppressed (paragraph 0003).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2014-74132
[0009] Patent Document 2: Japanese Patent Application Publication No. 2000-239616 Summary of the invention
[0010] Technical problem to be solved by the invention
[0011] However, in the resin compositions described in Patent Documents 1 and 2, semiconductor devices formed by bonding a semiconductor element to a substrate may not exhibit good conductivity over a long period of time, and there is room for improvement in long-term reliability.
[0012] Technical solutions for solving technical problems
[0013] The inventors of the present invention have found that a semiconductor device exhibits good conductivity over a long period of time and is excellent in long-term reliability by using a (meth)acryloyl group-containing compound having a predetermined structure, thereby completing the present invention.
[0014] The present invention can be described as follows.
[0015] According to the present invention, there is provided a paste-like resin composition comprising:
[0016] (A) a (meth)acryloyl group-containing compound having two or more functional groups and having a linear or branched oxyalkylene group having two or more repeating units; and
[0017] (B) Metal-containing particles comprising silver-containing particles or copper-containing particles.
[0018] According to the present invention, there is provided a high thermal conductive material obtained by sintering the paste-like resin composition.
[0019] According to the present invention, there is provided a semiconductor device comprising: a substrate; and a semiconductor element mounted on the substrate via an adhesive layer, wherein the adhesive layer is formed by sintering the paste-like resin composition.
[0020] Effects of the Invention
[0021] According to the present invention, a paste-like resin composition can be provided, which can be used for bonding a semiconductor element and a substrate to obtain a semiconductor device that exhibits good conductivity over a long period of time and has excellent long-term reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a cross-sectional view schematically showing an example of a semiconductor device.
[0023] Figure 2 It is a cross-sectional view schematically showing an example of a semiconductor device. DETAILED DESCRIPTION
[0024] Hereinafter, the embodiments of the present invention will be described using the accompanying drawings. In addition, in all the accompanying drawings, the same components are marked with the same symbols, and the description is appropriately omitted. In addition, unless otherwise specified, "to" means "above" to "below".
[0025] The paste-like resin composition of the present embodiment contains: (A) a (meth)acryloyl group-containing compound having two or more functional groups and having two or more repeating units of linear or branched oxyalkylene groups; and (B) metal particles containing silver particles or copper particles.
[0026] [(Meth)acryloyl group-containing compound (A)]
[0027] The (meth)acryloyl group-containing compound (A) can be used without particular limitation as long as it has a (meth)acryloyl group having two or more functional groups and a linear or branched oxyalkylene group having two or more repeating units, within a range where the effects of the present invention can be exhibited.
[0028] In this embodiment, by using a paste-like resin composition containing a (meth)acryloyl compound (A) having this structure, the stress of the material obtained by sintering the composition is relaxed, and the toughness is also excellent (high fracture energy, difficult to break). Therefore, it can be considered that the semiconductor device formed by joining the semiconductor element and the substrate by the paste-like resin composition of this embodiment can suppress the peeling of the joint part, etc., and show good conductivity for a long time, and has excellent long-term reliability.
[0029] The number of repeating units of the oxyalkylene group can be 2 or more, preferably 4 or more, more preferably 4 to 30, and particularly preferably 8 to 30 from the viewpoint of the effects of the present invention.
[0030] Examples of the oxyalkylene group include linear or branched oxyalkylene groups having 2 to 10 carbon atoms, preferably linear or branched oxyalkylene groups having 2 to 8 carbon atoms, and more preferably linear or branched oxyalkylene groups having 2 to 5 carbon atoms.
[0031] In the present embodiment, the (meth)acryloyl group-containing compound (A) preferably contains at least one selected from the group consisting of compounds represented by the following general formula (1).
[0032]
[0033] In the general formula (1), R represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and a plurality of Rs present may be the same or different.
[0034] X represents a hydrogen atom, a halogen atom, a hydroxyl group, an amino group, a cyano group, a mercapto group, a carboxyl group, an alkyl group having 1 to 3 carbon atoms, or an alkoxy group having 1 to 3 carbon atoms, and is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. Multiple Xs may be the same or different.
[0035] m can represent an integer of 2-10, preferably an integer of 2-8, and more preferably an integer of 2-5.
[0036] n can represent an integer of 4 to 30, and preferably represents an integer of 8 to 30.
[0037] Examples of the (meth)acryloyl-containing compound (A) include diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol #200 di(meth)acrylate (n: 4), polyethylene glycol #400 di(meth)acrylate (n: 9), polyethylene glycol #600 di(meth)acrylate (n: 14), polyethylene glycol #1000 di(meth)acrylate (n: 23), and the like.
[0038] From the viewpoint of the effects of the present invention, the (meth)acryloyl group-containing compound (A) may be contained in an amount of 0.1 to 15 wt %, preferably 0.5 to 10 wt %, more preferably 1.0 to 8 wt % in the total nonvolatile components of the paste resin composition.
[0039] Furthermore, within the range not affecting the effects of the present invention, a (meth)acryloyl-containing compound other than the (meth)acryloyl-containing compound (A) such as a monofunctional (meth)acrylic monomer having only one (meth)acryloyl group in one molecule may be contained together with the (meth)acryloyl-containing compound (A).
[0040] [Metallic particles (B)]
[0041] The metal-containing particles (B) can be sintered by appropriate heat treatment to form a particle-connected structure (sintered structure).
[0042] The metal-containing particles (B) can contain silver-containing particles or copper-containing particles.
[0043] In particular, by including silver particles in the paste resin composition, especially silver particles with a small particle size and a large specific surface area, a sintered structure can be easily formed even when heat treated at a relatively low temperature (about 180° C.) The preferred particle size will be described later.
[0044] The shape of the metal-containing particles (B) is not particularly limited. A preferred shape is spherical, but a non-spherical shape such as an ellipsoid, flat, plate, flake, or needle may also be used.
[0045] (“Spherical” is not limited to a perfect sphere, but also includes shapes with slight bumps on the surface. The same applies to the following in this specification.)
[0046] The metal-containing particles (B) may be (i) particles consisting essentially of metal alone, or (ii) particles consisting of metal and components other than metal. Furthermore, the metal-containing particles may be used in combination with (i) and (ii).
[0047] In this embodiment, the metal-containing particles (B) preferably include metal-coated resin particles in which the surfaces of the resin particles are coated with metal. Therefore, a paste-like resin composition that can produce a cured product having better thermal conductivity and better storage elastic modulus can be prepared.
[0048] The metal-coated resin particles have a metal surface and a resin inside, so they have good thermal conductivity and are softer than particles composed only of metal. Therefore, by using metal-coated resin particles, it is easy to design the thermal conductivity and storage elastic modulus to appropriate values.
[0049] Generally, in order to improve thermal conductivity, it is possible to consider increasing the amount of metal-containing particles. However, generally, since metal is "hard", if the amount of metal-containing particles is too much, the elastic modulus after sintering sometimes becomes too large. By using a part or all of the metal-containing particles as metal-coated resin particles, it is possible to easily design a paste-like resin composition that can obtain a cured product having a desired thermal conductivity and storage elastic modulus.
[0050] In the metal-coated resin particles, the metal layer only needs to cover at least a portion of the surface of the resin particles. Of course, the metal layer may cover the entire surface of the resin particles.
[0051] Specifically, in the metal-coated resin particles, the metal layer preferably covers 50% or more, more preferably 75% or more, and further preferably 90% or more of the surface of the resin particles. In the metal-coated resin particles, the metal layer preferably covers substantially the entire surface of the resin particles.
[0052] From another perspective, when the metal-coated resin particles are cut at a certain cross section, it is preferable that the metal layer be confirmed all around the cross section.
[0053] As another viewpoint, the mass ratio of resin / metal in the metal-coated resin particles is, for example, 90 / 10 to 10 / 90, preferably 80 / 20 to 20 / 80, and more preferably 70 / 30 to 30 / 70.
[0054] The "metal" in the metal-coated resin particles is as described above. Silver is particularly preferred.
[0055] Examples of the "resin" in the metal-coated resin particles include silicone resins, (meth) acrylic resins, phenolic resins, polystyrene resins, melamine resins, polyamide resins, and polytetrafluoroethylene resins. Of course, other resins may also be used. Furthermore, the resin may be only one type, or two or more types of resins may be used in combination.
[0056] From the viewpoint of elastic properties and heat resistance, the resin is preferably a silicone resin or a (meth)acrylic resin.
[0057] The silicone resin may be particles composed of an organopolysiloxane obtained by polymerizing an organochlorosilane such as methylchlorosilane, trimethyltrichlorosilane, or dimethyldichlorosilane, or may be an organosilicone resin having a structure obtained by further three-dimensionally crosslinking the organopolysiloxane as a basic skeleton.
[0058] (Meth) acrylic resin can contain 50% by weight or more, preferably 70% by weight or more, and more preferably 90% by weight or more of a resin obtained by polymerizing a monomer containing (meth) acrylic acid ester as a main component. As (meth) acrylic acid ester, for example, methyl (meth) acrylate, ethyl (meth) acrylate, propyl (meth) acrylate, butyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, lauryl (meth) acrylate, stearyl (meth) acrylate, cyclohexyl (meth) acrylate, 2-hydroxyethyl (meth) acrylate, 2-propyl (meth) acrylate, chloro-2-hydroxyethyl (meth) acrylate, diethylene glycol mono(meth) acrylate, methoxyethyl (meth) acrylate, glycidyl (meth) acrylate, dicyclopentyl (meth) acrylate, dicyclopentenyl (meth) acrylate and at least one compound in isobornyl (meth) acrylate. In addition, the monomer component of acrylic resin can contain a small amount of other monomers. As these other monomer components, for example, styrene monomers can be mentioned. Regarding the metal-coated (meth)acrylic resin, reference may also be made to the description of Japanese Patent Application Laid-Open No. 2017-126463 and the like.
[0059] Various functional groups can be introduced into silicone resins and (meth)acrylic resins. The functional groups that can be introduced are not particularly limited. Examples thereof include epoxy, amino, methoxy, phenyl, carboxyl, hydroxyl, alkyl, vinyl, and mercapto groups.
[0060] The resin particle portion of the metal-coated resin particle may contain various additives, such as a low stress modifier, etc. Examples of the low stress modifier include butadiene styrene rubber, butadiene acrylonitrile rubber, polyurethane rubber, polyisoprene rubber, acrylic rubber, fluororubber, liquid organopolysiloxane, liquid polybutadiene and other liquid synthetic rubbers, etc. In particular, when the resin particle portion contains an organosilicon resin, the elastic properties of the metal-coated resin particle can be improved by containing a low stress modifier.
[0061] The shape of the resin particles in the metal-coated resin particles is not particularly limited. The preferred shape is spherical, but it may be a different shape other than spherical, such as flat, plate-like, needle-like, etc. When the metal-coated resin particles are formed into a spherical shape, it is preferred that the shape of the resin particles used is also spherical.
[0062] The specific gravity of the metal-coated resin particles is not particularly limited, and the lower limit is, for example, 2 or more, preferably 2.5 or more, and more preferably 3 or more. The upper limit of the specific gravity is, for example, 10 or less, preferably 9 or less, and more preferably 8 or less. The appropriate specific gravity refers to the preferred dispersibility of the metal-coated resin particles themselves, and the uniformity when the metal-coated resin particles and other metal-containing particles are used together.
[0063] When metal-coated resin particles are used, the proportion of the metal-coated resin particles in the total metal-containing particles (B) is preferably 1 to 50% by mass, more preferably 3 to 45% by mass, and further preferably 5 to 40% by mass. By appropriately adjusting this proportion, it is possible to further improve heat dissipation while suppressing a decrease in adhesive strength due to thermal cycling.
[0064] Incidentally, when the ratio of the metal-coated resin particles in the entire metal-containing particles (B) is not 100% by mass, the metal-containing particles other than the metal-coated resin particles are, for example, particles substantially composed only of metal.
[0065] Median particle size D of the metal-containing particles (B) (when a plurality of types of metal-containing particles are used in combination, the whole) 50 For example, it is 0.001 to 1000 μm, preferably 0.01 to 100 μm, and more preferably 0.1 to 20 μm. 50 Setting D to an appropriate value makes it easy to maintain a balance among thermal conductivity, sinterability, and resistance to thermal cycles. 50 By setting it to an appropriate value, it is possible to improve the workability of coating / bonding.
[0066] The particle size distribution of the metal-containing particles (horizontal axis: particle diameter, vertical axis: frequency) may be unimodal or multimodal.
[0067] The median particle size D of particles consisting essentially only of metal 50 For example, it is 0.8 μm or more, preferably 1.0 μm or more, and more preferably 1.2 μm or more. Therefore, the thermal conductivity can be further improved.
[0068] In addition, the median particle size D of particles consisting essentially of metal alone is 50 For example, it is 7.0 μm or less, preferably 5.0 μm or less, and more preferably 4.0 μm or less. Therefore, it is possible to further improve the sinterability and the uniformity of sintering.
[0069] Median particle size D of metal-containing particles (B) 50 For example, it is 0.5 μm or more, preferably 1.5 μm or more, and more preferably 2.0 μm or more. Therefore, it is easy to set the storage elastic modulus E' to an appropriate value.
[0070] In addition, the median particle size D of the metal-containing particles (B) is 50 For example, it is 20 μm or less, preferably 15 μm or less, and more preferably 10 μm or less. Therefore, it is easy to sufficiently improve the thermal conductivity.
[0071] Median particle size D of metal-containing particles (B) 50 For example, it can be determined by measuring particle images using a flow particle image analyzer FPIA (registered trademark)-3000 manufactured by Sysmex Corporation. More specifically, the particle size of the metal-containing particles (B) can be determined by wet measuring the volume-based median diameter using this device.
[0072] The proportion of the metal-containing particles (B) in the paste resin composition as a whole (the total of these when multiple metal-containing particles are used) is, for example, 1 to 98% by mass, preferably 30 to 95% by mass, and more preferably 50 to 90% by mass. By setting the proportion of the metal-containing particles to 1% by mass or more, it is easy to improve thermal conductivity. By setting the proportion of the metal-containing particles (B) to 98% by mass or less, the workability of coating / bonding can be improved.
[0073] Among the metal-containing particles (B), particles consisting essentially of only metal can be obtained from, for example, Dowa Hightech Co., Ltd., Fukuda Metal Foil Powder Industry Co., Ltd., etc. In addition, metal-coated resin particles can be obtained from, for example, Mitsubishi Materials Corporation, Sekisui Chemical Co., Ltd., Sanno Co., Ltd., etc.
[0074] [Thermosetting resin (C)]
[0075] The paste-like resin composition of this embodiment may further contain a thermosetting resin (C). In this embodiment, the thermosetting resin (C) does not contain the (meth)acryloyl group-containing compound (A).
[0076] Thermosetting resin (C) generally contains a group that polymerizes / crosslinks by causing active chemical species such as free radicals to act and / or a chemical structure that reacts with a curing agent (D) described below. Thermosetting resin (C) contains, for example, one or more of an epoxy group, an oxetanyl group, a group containing an olefinic carbon-carbon double bond, a hydroxyl group, an isocyanate group, a maleimide structure, and the like.
[0077] As the thermosetting resin (C), epoxy resin is preferably used.
[0078] The epoxy resin may be a compound having only one epoxy group in one molecule, or may be a compound having two or more epoxy groups in one molecule.
[0079] Examples of the epoxy resin include bifunctional or crystalline epoxy resins such as biphenyl-type epoxy resins, bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, stilbene-type epoxy resins, and hydroquinone-type epoxy resins; novolac-type epoxy resins such as cresol novolac-type epoxy resins, phenol novolac-type epoxy resins, and naphthol novolac-type epoxy resins; phenol aralkyl-type epoxy resins such as phenylene skeleton-containing phenol aralkyl-type epoxy resins, biphenylene skeleton-containing phenol aralkyl-type epoxy resins, and phenylene skeleton-containing naphthol aralkyl-type epoxy resins; trifunctional epoxy resins such as trisphenol methane-type epoxy resins and alkyl-modified trisphenol methane-type epoxy resins; modified phenol-type epoxy resins such as dicyclopentadiene-modified phenol-type epoxy resins and terpene-modified phenol-type epoxy resins; heterocyclic epoxy resins such as triazine core-containing epoxy resins, and the like.
[0080] Moreover, as an epoxy group-containing compound, a monofunctional epoxy group-containing compound such as 4-tert-butylphenyl glycidyl ether, m-cresyl glycidyl ether, p-cresyl glycidyl ether, phenyl glycidyl ether, and cresyl glycidyl ether may be included.
[0081] The paste-like resin composition of the present embodiment may contain only one type of thermosetting component, or may contain two or more types of thermosetting components.
[0082] In the present embodiment, it is preferred that the thermosetting resin (C) and the (meth)acryloyl-containing compound (A) are used in combination. The ratio (mass ratio) when these are used in combination is not particularly limited, for example, the thermosetting resin (C) / (meth)acryloyl-containing compound (A) = 95 / 5 to 50 / 50, preferably the thermosetting resin (C) / (meth)acryloyl-containing compound (A) = 90 / 10 to 60 / 40.
[0083] As the thermosetting resin (C), an epoxy resin is preferred. As the epoxy resin, preferably, bisphenol A type epoxy resin, bisphenol F type epoxy resin, etc. can be mentioned.
[0084] The amount of the thermosetting resin (C) in the paste-like resin composition of the present embodiment is, for example, 3 to 20 mass %, or preferably 5 to 15 mass % in the entire non-volatile components.
[0085] [Curing agent (D)]
[0086] The paste-like resin composition of this embodiment may further contain a curing agent (D).
[0087] Examples of the curing agent (D) include a curing agent having a reactive group that reacts with the thermosetting resin (C). The curing agent (D) contains, for example, a reactive group that reacts with a functional group such as an epoxy group, a maleimide group, or a hydroxyl group contained in the thermosetting resin (C).
[0088] The curing agent (D) preferably contains a phenolic curing agent and / or an imidazole curing agent. These curing agents are particularly preferred when the thermosetting component contains an epoxy group.
[0089] The phenolic curing agent may be a low molecular weight compound or a high molecular weight compound (ie, a phenolic resin).
[0090] Examples of the low molecular weight phenolic curing agent include bisphenol compounds such as bisphenol A and bisphenol F (dihydroxydiphenylmethane) (phenol resins having a bisphenol F skeleton); and compounds having a biphenylene skeleton such as 4,4′-bisphenol.
[0091] Specific examples of the phenolic resin include: novolac-type phenolic resins such as phenol novolac resins, cresol novolac resins, bisphenol novolac resins, and phenol-biphenyl novolac resins; polyfunctional phenolic resins such as polyvinylphenol; triphenylmethane-type phenolic resins; modified phenolic resins such as terpene-modified phenolic resins and dicyclopentadiene-modified phenolic resins; phenol aralkyl-type phenolic resins such as phenol aralkyl resins having a phenylene skeleton and / or a biphenylene skeleton, and naphthol aralkyl resins having a phenylene and / or a biphenylene skeleton.
[0092] When using a curing agent (D), only one kind may be used, or two or more kinds may be used in combination.
[0093] When the paste-like resin composition of the present embodiment contains a curing agent (D), the amount thereof is, for example, 10 to 150 parts by mass, or preferably 20 to 100 parts by mass, based on 100 parts by mass of the thermosetting resin (C).
[0094] (Curing accelerator)
[0095] The paste-like resin composition of the present embodiment may further contain a curing accelerator.
[0096] Typically, the curing accelerator is a curing accelerator that accelerates the reaction of the thermosetting resin (C) and the curing agent (D).
[0097] Specific examples of curing accelerators include: compounds containing phosphorus atoms, such as organic phosphines, tetrasubstituted phosphonium compounds, phosphobetaine compounds, adducts of phosphine compounds and quinone compounds, and adducts of phosphonium compounds and silane compounds; amidines and tertiary amines, such as dicyandiamide, 1,8-diazabicyclo[5.4.0]undecene-7, and benzyldimethylamine; and nitrogen atom-containing compounds, such as quaternary ammonium salts of the above amidines or tertiary amines.
[0098] When using a curing accelerator, only one type may be used, or two or more types may be used in combination.
[0099] When the paste-like resin composition of the present embodiment contains a curing accelerator, the amount thereof is, for example, 0.1 to 10 parts by mass, or preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the thermosetting resin (C).
[0100] (Silane coupling agent)
[0101] The paste-like resin composition of the present embodiment may further contain a silane coupling agent, thereby further improving the adhesive force.
[0102] As the silane coupling agent, known silane coupling agents may be mentioned, and specifically, vinyl silanes such as vinyltrimethoxysilane and vinyltriethoxysilane may be mentioned;
[0103] Epoxysilanes such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane; styrylsilanes such as p-styryltrimethoxysilane;
[0104] Methacryl silanes such as 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropyltriethoxysilane;
[0105] Acrylic silanes such as 3-(trimethoxysilyl)propyl methacrylate and 3-acryloxypropyltrimethoxysilane;
[0106] Aminosilanes such as N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane;
[0107] Isocyanate silane;
[0108] Alkyl silane;
[0109] Urea silanes such as 3-ureidopropyltrialkoxysilane;
[0110] Mercaptosilanes such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane;
[0111] Isocyanate silanes such as 3-isocyanatepropyltriethoxysilane and the like.
[0112] When using a silane coupling agent, only one type may be used, or two or more types may be used in combination.
[0113] When the paste resin composition of the present embodiment contains a silane coupling agent, the amount is, for example, 0.1 to 10 parts by mass, preferably 0.5 to 5 parts by mass, when the amount of the thermosetting component (the total amount of the (meth)acryloyl compound (A) and the thermosetting resin (C)) is 100 parts by mass.
[0114] (Plasticizer)
[0115] The paste-like resin composition of this embodiment may contain a plasticizer. The plasticizer makes it easy to design the storage elastic modulus to be small and further suppress the decrease in adhesive force due to thermal cycles.
[0116] Specific examples of the plasticizer include polyester compounds, silicone oils, silicone compounds such as silicone rubber, polybutadiene compounds such as polybutadiene maleic anhydride adducts, and acrylonitrile-butadiene copolymer compounds.
[0117] When using a plasticizer, only one type may be used, or two or more types may be used in combination.
[0118] When the paste resin composition of the present embodiment contains a plasticizer, the amount is, for example, 5 to 50 parts by mass, preferably 10 to 30 parts by mass, when the amount of the thermosetting component (the total amount of the (meth)acryloyl compound (A) and the thermosetting resin (C)) is set to 100 parts by mass.
[0119] (Free Radical Initiator)
[0120] The paste-like resin composition of the present embodiment may contain a radical initiator.
[0121] The radical initiator may, for example, suppress insufficient curing, allow the curing reaction to proceed sufficiently at a relatively low temperature (eg, 180° C.), or further improve the adhesive force.
[0122] Examples of the radical initiator include peroxides and azo compounds.
[0123] Examples of the peroxide include organic peroxides such as diacyl peroxides, dialkyl peroxides, and peroxyketals. More specifically, examples include ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide; peroxyketals such as 1,1-di(tert-butylperoxy)cyclohexane and 2,2-di(4,4-di(tert-butylperoxy)cyclohexyl)propane;
[0124] Hydroperoxides such as p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, isopropylbenzene hydroperoxide, and tert-butyl hydroperoxide;
[0125] Dialkyl peroxides such as di(2-tert-butylperoxyisopropyl)benzene, diisopropylphenyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butylisopropylphenyl peroxide, di-tert-hexyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, and di-tert-butyl peroxide;
[0126] Diacyl peroxides such as dibenzoyl peroxide and di(4-methylbenzoyl) peroxide;
[0127] Peroxydicarbonates such as di-n-propyl peroxydicarbonate and diisopropyl peroxydicarbonate;
[0128] Peroxyesters such as 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-hexyl peroxybenzoate, tert-butyl peroxybenzoate, and tert-butyl peroxy 2-ethylhexanoate.
[0129] Examples of the azo compound include 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), and 2,2'-azobis(2,4-dimethylvaleronitrile).
[0130] When using a radical initiator, only one type may be used, or two or more types may be used in combination.
[0131] In the case where the paste resin composition of the present embodiment contains a free radical initiator, when the amount of the thermosetting component (including the total amount of the (meth)acryloyl compound (A) and the thermosetting resin (C)) is set to 100 parts by mass, the amount is, for example, 0.1 to 10 parts by mass, preferably 0.5 to 8 parts by mass, and more preferably 0.5 to 5 parts by mass.
[0132] (Solvent)
[0133] The paste-like resin composition of the present embodiment may further contain a solvent. The solvent can be used to adjust the fluidity of the paste-like resin composition, improve workability when forming an adhesive layer on a substrate, and the like.
[0134] Typically, the solvent is an organic solvent.
[0135] Examples of the organic solvent include alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, methyl methoxybutanol, α-terpineol, β-terpineol, hexylene glycol, benzyl alcohol, 2-phenylethyl alcohol, isopalmityl alcohol, isostearyl alcohol, lauryl alcohol, ethylene glycol, propylene glycol, butylpropylene triglycol, and glycerin;
[0136] Ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, diacetone alcohol (4-hydroxy-4-methyl-2-pentanone), 2-octanone, isophorone (3,5,5-trimethyl-2-cyclohexene-1-one), and diisobutyl ketone (2,6-dimethyl-4-heptanone);
[0137] Ethyl acetate, butyl acetate, diethyl phthalate, dibutyl phthalate, acetoxyethane, methyl butyrate, methyl caproate, methyl octanoate, methyl decanoate, methyl cellosolve acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, 1,2-diacetoxyethane, tributyl phosphate, tricresyl phosphate, tripentyl phosphate and other esters;
[0138] Ethers such as tetrahydrofuran, dipropyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, propylene glycol dimethyl ether, ethoxyethyl ether, 1,2-bis(2-diethoxy)ethane, and 1,2-bis(2-methoxyethoxy)ethane;
[0139] Ester ethers such as 2-(2-butoxyethoxy)ethane acetate;
[0140] 2-(2-methoxyethoxy)ethanol and other ether alcohols;
[0141] Toluene, xylene, normal alkanes, isoalkanes, dodecylbenzene, turpentine, kerosene, light oil and other hydrocarbons;
[0142] Nitriles such as acetonitrile or propionitrile;
[0143] Acetamide, N,N-dimethylformamide and other amides;
[0144] Low molecular weight volatile silicone oil, volatile organic modified silicone oil and other silicone oils, etc.
[0145] When a solvent is used, only one type of solvent may be used, or two or more types of solvents may be used in combination.
[0146] When a solvent is used, the amount thereof is not particularly limited and the amount used may be appropriately adjusted based on desired fluidity, etc. As an example, the solvent is used in an amount such that the non-volatile component concentration of the paste-like resin composition becomes 50 to 90% by mass.
[0147] (Properties of the composition)
[0148] The paste resin composition of this embodiment is preferably paste-like at 20° C. That is, the paste resin composition of this embodiment can be applied to a substrate or the like like a paste at 20° C. Therefore, the paste resin composition of this embodiment can be preferably used as an adhesive for semiconductor elements or the like.
[0149] Of course, depending on the process to be applied, etc., the paste-like resin composition of this embodiment may be in the form of a varnish having a relatively low viscosity.
[0150] <High thermal conductivity materials>
[0151] A highly thermally conductive material can be obtained by sintering the paste-like resin composition of the present embodiment.
[0152] By changing the shape of the high thermal conductivity material, it can be applied to various parts that require heat dissipation in the automotive and motor fields.
[0153] <Semiconductor devices>
[0154] The paste-like resin composition of this embodiment can be used to manufacture a semiconductor device. For example, a semiconductor device can be manufactured by using the paste-like resin composition of this embodiment as an "adhesive" between a substrate and a semiconductor element.
[0155] In other words, the semiconductor device of the present embodiment includes, for example, a substrate and a semiconductor element mounted on the substrate via an adhesive layer obtained by sintering the paste-like resin composition by heat treatment.
[0156] In the semiconductor device of this embodiment, the adhesion of the adhesive layer is not easily degraded by heat cycles. That is, the semiconductor device of this embodiment has high reliability.
[0157] Examples of semiconductor elements include ICs, LSIs, power semiconductor elements (power semiconductors), and other various elements.
[0158] Examples of the substrate include various semiconductor wafers, lead frames, BGA substrates, mounting substrates, heat spreaders, heat sinks, and the like.
[0159] Hereinafter, an example of a semiconductor device will be described with reference to the drawings.
[0160] Figure 1is a cross-sectional view showing an example of a semiconductor device.
[0161] The semiconductor device 100 includes a substrate 30 and a semiconductor element 20 mounted on the substrate 30 via an adhesive layer 10 (die bonding material) which is a heat-treated body of a paste-like resin composition.
[0162] The semiconductor element 20 and the substrate 30 are electrically connected to each other via, for example, a bonding wire 40 or the like. In addition, the semiconductor element 20 is sealed with, for example, a sealing resin 50 .
[0163] The thickness of the adhesive layer 10 is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more. Therefore, the stress absorption capacity of the paste-like resin composition can be increased, and the heat cycle resistance can be improved.
[0164] The thickness of the adhesive layer 10 is, for example, 100 μm or less, or preferably 50 μm or less.
[0165] Figure 1 In the embodiment, the substrate 30 is, for example, a lead frame. At this time, the semiconductor element 20 is mounted on the die pad 32 or the substrate 30 via the adhesive layer 10. In addition, the semiconductor element 20 is electrically connected to the outer lead 34 (substrate 30) via, for example, a bonding wire 40. The substrate 30 as a lead frame is, for example, made of 42 alloy, Cu frame, etc.
[0166] The substrate 30 may be an organic substrate or a ceramic substrate. Examples of the organic substrate include organic substrates made of epoxy resin, cyanate resin, maleimide resin, and the like.
[0167] The surface of the base material 30 may be coated with a metal such as silver or gold, for example, so as to improve the adhesion between the adhesive layer 10 and the base material 30 .
[0168] Figure 2 It means Figure 1 A cross-sectional view of an example of a different semiconductor device 100 .
[0169] exist Figure 2 In the semiconductor device 100, the substrate 30 is, for example, an interposer. A plurality of solder balls 52 are formed on the surface of the substrate 30 as an interposer opposite to the surface on which the semiconductor element 20 is mounted. At this time, the semiconductor device 100 is connected to another wiring board via the solder balls 52.
[0170] An example of a method for manufacturing a semiconductor device will be described.
[0171] First, a paste-like resin composition is applied on the base material 30, and then the semiconductor element 20 is placed thereon. That is, the base material 30, the paste-like resin composition, and the semiconductor element 20 are stacked in this order.
[0172] The method for applying the paste-like resin composition is not particularly limited, and specific examples thereof include a dispensing method, a printing method, and an inkjet method.
[0173] Next, the paste resin composition is thermally cured. Thermal curing is preferably performed by pre-curing and post-curing. By thermal curing, the paste resin composition becomes a heat-treated body (cured product). By thermal curing (heat treatment), the metal-containing particles in the paste resin composition are agglomerated, and a structure in which the interfaces of multiple metal-containing particles disappear in the adhesive layer 10 is formed. Therefore, the substrate 30 and the semiconductor element 20 are bonded via the adhesive layer 10. Next, the semiconductor element 20 and the substrate 30 are electrically connected using the bonding wire 40. Next, the semiconductor element 20 is sealed with a sealing resin 50. In this way, a semiconductor device can be manufactured.
[0174] The embodiments of the present invention are described above, but these are only examples of the present invention, and various structures other than the above may be adopted. Furthermore, the present invention is not limited to the above embodiments, and modifications and improvements within the scope of achieving the purpose of the present invention are included in the present invention.
[0175] Example
[0176] Embodiments of the present invention will be described in detail based on Examples and Comparative Examples. The present invention is not limited to Examples.
[0177] <Preparation of Pasty Resin Composition>
[0178] First, each raw material component was mixed according to the blending amount shown in Table 1 described later to obtain a varnish.
[0179] Next, the varnish, solvent, and metal-containing particles (including metal-coated resin particles) were blended in the amounts shown in Table 1 described below and kneaded using a three-roll mill at room temperature to prepare a paste-like resin composition.
[0180] The information of raw material components in Table 1 is shown below.
[0181] (Thermosetting component)
[0182] Epoxy resin 1: Bisphenol F type liquid epoxy resin (manufactured by Nippon Kayaku Co., Ltd., RE-303S)
[0183] (Curing agent)
[0184] Curing agent 1: Phenolic resin having a bisphenol F skeleton (solid at room temperature 25°C, manufactured by DIC Corporation, DIC-BPF)
[0185] ((Meth)acryloyl compounds)
[0186] Acrylic monomer 1: ethylene glycol dimethacrylate (manufactured by Kyoei Chemical Co., Ltd., LIGHT ESTEREG)
[0187] Acrylic acid monomer 2: polyethylene glycol #600 dimethacrylate (n in the general formula (1) is 14) (manufactured by NOF Corporation, PDE600)
[0188] Acrylic monomer 3: polyethylene glycol #600 dimethacrylate (n in the general formula (1) is 14) (manufactured by Kyoei Chemical Co., Ltd., LIGHT ESTER 14EG)
[0189] Acrylic acid monomer 4: polyethylene glycol #1000 diacrylate (n in the general formula (1) is 23) (manufactured by Shin-Nakamura Chemical Co., Ltd., A-1000)
[0190] (Plasticizer)
[0191] Plasticizer 1: Allyl resin (manufactured by Kanto Chemical Co., Ltd., polymer of bis(2-propenyl)-1,2-cyclohexanedicarboxylate and propane-1,2-diol)
[0192] (Curing accelerator)
[0193] Imidazole curing agent 1: 2-phenyl-1H-imidazole-4,5-dimethanol (manufactured by Shikoku Chemical Industry Co., Ltd., 2PHZ-PW)
[0194] (Polymerization initiator)
[0195] Radical polymerization initiator 1: diisopropylphenyl peroxide (manufactured by Kayaku Akzo Corporation, Perkadox BC)
[0196] (Contains metal particles)
[0197] Silver particles 1: Silver powder (manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., HKD-38, flake, D 50 :4μm)
[0198] Silver-coated resin particles 1: Silver-coated silicone resin particles (Mitsubishi Materials Corporation, heat-resistant / surface-treated 10 μm product, spherical, D 50 : 10μm, specific gravity: 2.3, weight ratio of silver is 50wt%, weight ratio of resin is 50wt%)
[0199] (Solvent)
[0200] Solvent 1: Butyl tripropylene glycol (BFTG)
[0201] <Measurement of thermal conductivity λ>
[0202] The obtained paste resin composition was applied on a Teflon plate, heated from 30°C to 200°C over 60 minutes in a nitrogen atmosphere, and then heat treated at 200°C for 120 minutes. Thus, a heat-treated body of the paste resin composition having a thickness of 1 mm was obtained ("Teflon" is a registered trademark for fluororesin).
[0203] Next, the thermal diffusion coefficient α in the thickness direction of the heat-treated body was measured by a laser flash method at a measurement temperature of 25°C.
[0204] In addition, the specific heat Cp was measured by differential scanning calorimetry (DSC).
[0205] Furthermore, according to JIS K 6911, the density ρ was measured.
[0206] Using these values, the thermal conductivity λ was calculated based on the following formula.
[0207] Thermal conductivity λ[W / (m·K)]=α[m 2 / sec]×Cp[J / kg·K]×ρ[g / cm 3 ]
[0208] <Measurement of resistivity>
[0209] The obtained paste resin composition was applied on a glass plate, heated from 30°C to 200°C over 60 minutes in a nitrogen atmosphere, and then heat treated at 200°C for 120 minutes. Thus, a heat-treated body of the paste resin composition with a thickness of 0.05 mm was obtained. The resistance value of the surface of the heat-treated body was measured using a direct current four-electrode method based on a milliohm meter (manufactured by Hioki EE Corporation) and an electrode with an electrode spacing of 40 mm.
[0210] <Measurement of storage elastic modulus E' at 25°C>
[0211] The obtained paste-like resin composition was applied on a Teflon plate, and the temperature was raised from 30° C. to 200° C. over 60 minutes, and then heat-treated at 200° C. for 120 minutes. Thus, a heat-treated body of the thermally conductive composition having a thickness of 0.3 mm was obtained.
[0212] The heat-treated body was peeled from the Teflon plate and placed on a measuring device (DMS6100 manufactured by Hitachi High-Technologies Corporation) to perform dynamic viscoelasticity measurement (DMA) in a tensile mode at a frequency of 1 Hz. The storage elastic modulus E' (MPa) at 25°C was measured.
[0213] <Measurement of breaking strength>
[0214] The obtained paste resin composition was applied on a Teflon plate, heated from 30°C to 200°C over 60 minutes, and then heat treated at 200°C for 120 minutes. Thus, a heat-treated body of a thermally conductive composition having a thickness of 0.3 mm and a width of 4 mm was obtained. In addition, the breaking strength of each test sample at 25°C was measured using a tensile tester (manufactured by Shimadzu Corporation, "MST-1").
[0215] <Measurement of fracture strain>
[0216] The fracture strain was calculated by dividing the elongation from the origin of elongation (initial inter-chuck distance) to the fracture point of each test piece (the displacement amount when the test piece fractured) by the initial inter-chuck distance.
[0217] <Measurement of fracture energy>
[0218] The breaking point energy is calculated by integrating the stress from the origin of elongation (initial distance between the clamps) to the breaking point of each test piece (the amount of displacement when the test piece breaks) with the displacement. The breaking point energy obtained is divided by the volume of the test piece to obtain the breaking point energy per unit volume (mJ / mm 3 ).
[0219] <Thermal cycle test / evaluation of peeling>
[0220] The paste resin composition was applied to a silver-plated substrate to form a coating film, and a 7×7 mm silicon chip with a gold-plated surface was placed on the coating film. Thereafter, the temperature was raised from 30°C to 200°C over 60 minutes, and then heat-treated at 200°C for 120 minutes. Thus, the thermally conductive composition was cured, and the silicon chip was bonded to the substrate.
[0221] The bonded silicon chip / substrate was sealed with a sealing material EME-G700ML-C (manufactured by Sumitomo Bakelite Co., Ltd.) and used as a sample for a temperature cycle test.
[0222] The sample was placed in a high temperature and high humidity tank at 60°C / 60%RH for 48 hours, and then subjected to a reflow treatment at 260°C.
[0223] The sample after the reflow treatment was placed in a temperature cycle tester TSA-72ES (manufactured by ESPEC CORP.) and subjected to 2000 cycles of (i) 150°C / 10 minutes, (ii) 25°C / 10 minutes, (iii) -65°C / 10 minutes, and (iv) 25°C / 10 minutes.
[0224] Thereafter, the presence or absence of peeling was checked by SAT (ultrasonic testing). The case where no peeling occurred was evaluated as ○ (good), and the case where peeling occurred was evaluated as × (bad).
[0225] [Table 1]
[0226] Table-1
[0227]
[0228] From the results in Table 1, it is understood that by bonding a semiconductor element and a substrate using the paste-like resin composition of the present invention, a semiconductor device that exhibits good conductivity over a long period of time and has excellent long-term reliability can be obtained.
[0229] This application claims the benefit of priority based on Japanese patent application No. 2020-012506, filed on January 29, 2020, the disclosure of which is incorporated herein in its entirety by reference.
Claims
1. A paste resin composition, characterized in that contain: (A) a (meth)acryloyl group-containing compound comprising at least one compound selected from the group consisting of compounds represented by the following general formula (1); (B) silver particles or silver-coated resin particles; and (C) bisphenol F type epoxy resin, In the general formula (1), R represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and multiple R groups present may be the same or different; X represents a hydrogen atom, a halogen atom, a hydroxyl group, an amino group, a cyano group, a mercapto group, a carboxyl group, an alkyl group having 1 to 3 carbon atoms, or an alkoxy group having 1 to 3 carbon atoms, and multiple X groups present may be the same or different; m represents an integer of 2 to 10, and n represents an integer of 8 to 30.
2. The paste-like resin composition according to claim 1, characterized in that: It also contains a curing agent (D).
3. A high thermal conductivity material, characterized in that: The paste-like resin composition is obtained by sintering the paste-like resin composition according to claim 1 or 2.
4. A semiconductor device, characterized in that: have: Base material; and A semiconductor element is mounted on the substrate via an adhesive layer. The adhesive layer is formed by sintering the paste-like resin composition according to claim 1 or 2.
Citation Information
Patent Citations
Resin paste composition and semiconductor device using same
JP2000239616A
Conductive fine particle and method for producing conductive fine particle
JP2017126463A
Belt-type continuously variable transmission
JP2020012506A
Resin paste composition and semiconductor device
CN103013357A
Paste adhesive composition, semiconductor device, method for manufacturing semiconductor device, and method for bonding heat radiation plate
CN107207941A